Maßgeschneiderte Therapie der Virushepatitis der Gegenwart und Zukunft: Hepatitis B, C, Delta und E - Bartenschlager, Ralf; Cornberg, Markus; Pietschmann, Thomas (Der Internist, 2017)
Precision medicine is also possible for infectious diseases as shown for the treatment of chronic viral hepatitis, especially if different options are available. In hepatitis B virus (HBV) infection, treatment indication as well as the choice of treatment and the decisions to stop treatment are based on viral markers and alanine aminotransferase (ALT) level. Future therapies for HBV infection aiming for functional cure or even virus elimination may be even more personalized and have to take into account the immune status of a given patient. Such treatment modalities might also increase the chance for successful treatment of chronic hepatitis delta where treatment options are still very limited. Some new therapeutic concepts targeting host receptors or host enzymes are promising, but may require individualized approaches. Chronic hepatitis C is a good example for precision medicine based on viral and host factors. However, the main reason for individualized direct-acting antiviral (DAA) treatment is to save costs. As DAAs are effective in more than 95% of patients, elimination of HCV seems to be possible at the level of a given country or even on a global scale. However, owing to high reinfection rates in high-risk groups and limited availability of antiviral therapy in many high endemic countries, it must still be decided whether an HCV vaccine or pre-exposure prophylaxis is required to achieve this goal. Hepatitis E is an emerging topic as this is the most frequent acute hepatitis virus infection. It can result in a chronic infection in immunosuppressed individuals. Treatment options are still limited and individualized management is based on tailoring immunosuppressive therapy and therapy with ribavirin. Thus, personalized therapy of hepatitis E virus infection is still limited.
Gesehen am 01.10.2018